Molecular imaging in epilepsy - Koepp, Matthias (Henry Stewart Talks, 2011)
What is PET and how does it work, What can PET be used for?, The clinical impact of PET, The epileptogenic zone, Epileptogenic lesion, Functional deficit zone, Irritative zone, Seizure onset zone, Ictal symptomatogenic zone, Imaging co-morbidities, Imaging genetics